Implementation of Home–School Collaboration-Based Social Skills Training to Improve Social Communication in Children with Speech Delay - Muhammad Nuril Mukminin; Erizza Farizan Adani; Ribka Mutiara Simatupang (INCARE, International Journal of Educational Resources, 2026)
Social communication skills are a crucial aspect of child development, playing a vital role in forming interpersonal relationships, participating in learning activities, and adjusting to social environments. Children with speech delays often face challenges in social communication, such as difficulties initiating interactions, responding to others, and verbally requesting assistance. This study aims to describe the implementation of Social Skills Training (SST) based on home-school collaboration to enhance social communication in a child with a speech delay. A single-subject case study design with a mixed-methods approach was employed. The participant was a 7-year-4-month-old boy with a history of speech delay. The results showed an increase in the frequency of social communication behaviors, rising from a total of four behaviors during the baseline phase to 28 during the intervention—and the maintenance of these gains during the follow-up phase, with a total of 23 behaviors. These findings indicate that SST based on home-school collaboration can improve a child's social communication and facilitate the generalization of communication skills to daily life. Involvement of the child's natural environment is a key factor in the success of the intervention.